Watching the pennies: finances for freelancers. (June 2016) - Watts, Gillian
Abstract : This article offers financial tips for indexers who are self-employed, especially those who are new to freelancing. It stresses the importance of having a financial plan for your business and then watching the bottom line. The focus is on keeping track of your business's income and expenses, including invoicing, paying the bills, basic bookkeeping, banking and tax considerations.